Encapsulation of berberine decorated ZnO nano-colloids into injectable hydrogel using for diabetic wound healing - Yin, Xuechen; Fan, Xiangyi; Zhou, Zipeng; Li, Qi (Frontiers in Chemistry, 2022)
Chronic wound healing in diabetic patients had been considered a major clinical challenge, so there was an urgent need to establish more effective treatment methods. In this study, we prepared berberine-modified ZnO nano-colloids hydrogel (ZnO-Ber/H) and evaluated its wound healing performance in a diabetic rat. The prepared ZnO-Ber/H had excellent moisturizing, anti-inflammatory and anti-oxidative stress abilities. In vitro, ZnO-Ber/H could effectively up-regulate antioxidant stress factors (Nrf2, HO-1, NQO1) by 4.65-fold, 2.49-fold, 2.56-fold, respectively. In vivo experiments have shown that ZnO-Ber/H could effectively improve the wound healing rate (92.9%) after 15 days of treatment. Meanwhile, the ability of anti-oxidative stress had also been verified in vivo. ZnO-Ber/H down-regulated inflammatory factor (TNF-α, IL-1β, and IL-6) by 72.8%, 55% and 71% respectively, up-regulated vascular related factors VEGF and CD31 by 3.9-fold and 3.2-fold by Western blot. At the same time, ZnO-Ber/H could promote the expression of EGFR and FGFR, thereby affecting the generation of new epithelial tissue. Based on extensive characterization and biological evaluation, ZnO-Ber/H was expected to be a potential candidate for promoting diabetic wound healing.